Cannabinoids and Neurodegenerative Diseases - Romero, Julian; Martinez-Orgado, Jose (CNS & Neurological Disorders - Drug Targets, 2009)
Although significant advances have taken place in recent years on our understanding of the molecular mechanisms of different neurodegenerative diseases, its translation into effective therapeutic treatments has not been as successful as could be expected. There is still a dramatic lack of curative treatments for the most frequent disorders and only symptomatic relief for many others. Under this perspective, the search for novel therapeutic approaches is demanding and significant attention and efforts have been directed to studying additional neurotransmission systems including the endocannabinoid system (ECS). The neuroprotective properties of exogenous as well as endogenous cannabinoids have been known for years and the underlying molecular mechanisms have been recently unveiled. As discussed later, antioxidative, antiglutamatergic and antiinflammatory effects are now recognized as derived from cannabinoid action and are known to be of common interest for many neurodegenerative processes. Thus, these characteristics make cannabinoids attractive candidates for the development of novel therapeutic strategies [1]. The present review will focus on the existing data regarding the possible usefulness of cannabinoid agents for the treatment of relevant neurological pathologies for our society such as Alzheimer's disease, multiple sclerosis, Huntington's disease and amyotrophic lateral sclerosis.
Keywords: ischemia